Membangun Moralitas Generasi Muda untuk Menciptakan Pemimpin Masa Depan yang Beretika - Bintang, Nayya Hajar (Maliki Interdisciplinary Journal, 2025)
The morality of the younger generation plays a crucial role in shaping ethical future leaders. In the Islamic perspective morality serves as a foundation that integrates the relationship between humans and God as well as among individuals. This article explores efforts to build the morality of the younger generation through holistic Islamic educational management. This approach includes instilling Islamic values encouraging positive behavior modeling from parents and teachers and strengthening a supportive educational environment. Challenges such as the influence of globalization and the lack of attention to moral education are also key focuses. With an integrated strategy Islamic education can produce a young generation that is not only intellectually capable but also morally grounded to become responsible leaders committed to justice. This article provides practical recommendations to strengthen the roles of families schools and communities in supporting the moral development of the younger generation.